On policy interactions among nations: when do cooperation and commitment matter? - Hubert Kempf; Leopold von Thadden (European Central Bank (ECB), 2008)
This paper offers a framework to study commitment and cooperation issues in games with multiple policymakers. To reconcile some puzzles in the recent literature on the nature of policy interactions among nations, we prove that games characterized by different commitment and cooperation schemes can admit the same equilibrium outcome if certain spillover effects vanish at the common solution of these games. We provide a detailed discussion of these spillovers, showing that, in general, commitment and cooperation are non-trivial issues. Yet, in linear-quadratic models with multiple policymakers commitment and cooperation schemes are shown to become irrelevant under certain assumptions. The framework is suficiently general to cover a broad range of results from the recent literature on policy interactions as special cases, both within monetary unions and among fully sovereign nations.
Keywords: E52; E63; 330; fiscal regimes; monetary policy; Geldpolitik; Finanzpolitik; Internationale Wirtschaftspolitik; Spieltheorie; Theorie